The Effectiveness of Fulvestrant in postmenopausal advanced breast cancer; systematic review of clinical evidence - Amir Hashemi-Meshkini; Khosro Keshavarz; Mehdi Varmaghani; Abbas Kebriaeezadeh; Shekoufeh Nikfar (Tehran University of Medical Sciences, 2015)
Background: In this study we aim to assess the clinical evidence on the effectiveness of Fulvestrant compared with other alternatives to explore whether it has any advantage in the treatment outcomes of postmenopausal advanced breast cancer or not. Experimental: A systematic review was conducted through Medline, Scopus, ISI Web of Science and Google Scholar. The used keywords were "Fulvestrant" and "breast cancer", and the search was limited to articles published during 1990- 2012. The inclusion criteria were English language studies on advanced breast cancer and with one arm of Fulvestrant. The outcomes of interest included time to progression (TTP), objective response (OR), clinical benefit (CB), time to treatment failure (TTF) and overall survival (OS). Results: The included studies were classified into two groups based on the Fulvestrant arm: "Fulvestrant as single treatment strategy" and "Fulvestrant as combination treatment strategy". In the first group the included studies comparing Fulvestrant with Anastrozole (three reports), Exemestane (one report) and Tamoxifen (one report) indicated no significant advantage of Fulvestrant. In second group based on one study there was no significant difference between Anastrozol and Fulvestrant compared with Fulvestrant in terms of TTP, CB, OR, TTF, and OS and based on the second randomized controlled trial (RCT) the combination therapy was significantly more effective in term of OS and TTP but not CB and OR. Conclusion: Regarding the reviewed evidence, Fulvestrant neither as single treatment strategy compared with Exemestane, Anastrozole and Tamoxifen nor as combination treatment strategy by being added to Anastrozole could be considered advantageous in term of effectiveness.